TEACHERS' COMPETANCE TO TEACH PAECE EDUCATION AND IMPLEMENTATION OF PEACE EDUCATION IN PRIMARY SCHOOLS IN WARENG SUB-COUNTY, KENYA. - Molenje, Mary; Momanyi, Rose Kemunto; Mukwa, Prof. Chris; Barasa, Prof. Peter (IJRDO- Journal of Educational Research, 2018)
Kenya has experienced occasional times of conflict where members of various Kenyan communities have turned against one another. In an effort to address the issue of peace among Kenyan people, Peace Education (PE) was introduced in  primary schools in Kenya. Despite the introduction of the programme, little reference is made to the programme as issues of peace are discussed. This study therefore sought to assess the implementation of peace education in Wareng Sub County of  Uasin Gishu County. The study utilized the curriculum development and implementation theories by Gross et al (1971) and Fullan (1991). The study was guided by the following objective: to determine the relationship between competency of the teachers to teach the peace education and implementation of peace education. A survey research design was used  and the  mixed method approach was utilised to  collect data. The target population included primary school  head teachers and  teachers. The target population was stratified into three strata: head teachers and peace education/social studies  teachers. Purposeful and  Simple random sampling was used to obtain the respondents from each stratum. The study used questionnaires, interview schedules, focused group discussions  and document analysis to collect data. The relationships between the study variables were established using correlation coefficients. Multiple regression models were used to construct models that were used to explain the relationships. The study established that teacher competency influenced the teaching of peace education in primary schools. Research needs to be done to determine which other determinants influence the teaching of peace education.  The findings that were established can be used by curriculum developers, teachers of peace education, and by the ministry of education that can use the knowledge obtained to develop appropriate policies of peace education programmes and in service programmes for teachers of peace education.